2020
DOI: 10.1038/s41467-020-19462-w
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced fish production during a period of extreme global warmth

Abstract: Marine ecosystem models predict a decline in fish production with anthropogenic ocean warming, but how fish production equilibrates to warming on longer timescales is unclear. We report a positive nonlinear correlation between ocean temperature and pelagic fish production during the extreme global warmth of the Early Paleogene Period (62-46 million years ago [Ma]). Using data-constrained modeling, we find that temperature-driven increases in trophic transfer efficiency (the fraction of production passed up tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…These modifications in biomass of primary producers fuelled bottom-up energetic pathways through the food web and triggered a slight (about 1%) increase in biomass of higher trophic levels by medium-small pelagic fish groups. Similar projections have recently been obtained with the application of an end-to-end model in the Mediterranean as whole (Moullec et al, 2019) and have been suggested by other authors (Marquis et al, 2011) also in relation to past extreme global warming phases (Britten and Sibert, 2020). Keeping the fishing effort constant, the effect of climate change alone on landings and income per unit of effort was small but positive for all the fleets considered.…”
Section: Discussionsupporting
confidence: 87%
“…These modifications in biomass of primary producers fuelled bottom-up energetic pathways through the food web and triggered a slight (about 1%) increase in biomass of higher trophic levels by medium-small pelagic fish groups. Similar projections have recently been obtained with the application of an end-to-end model in the Mediterranean as whole (Moullec et al, 2019) and have been suggested by other authors (Marquis et al, 2011) also in relation to past extreme global warming phases (Britten and Sibert, 2020). Keeping the fishing effort constant, the effect of climate change alone on landings and income per unit of effort was small but positive for all the fleets considered.…”
Section: Discussionsupporting
confidence: 87%
“…This was associated with the colonization of different environments and the refilling of vacated functional roles (54-57) and included short-lived "evolutionary experiments" found alongside familiar living lineages (58,59). As with the mid-Cretaceous, the early Paleocene represented a "hothouse" period in Earth's climate history, with evidence that higher temperatures might have led to increased fish production in some marine settings (60). Collectively, these observations suggest a role for environmental change and ecosystem reorganization in facilitating the diversification of teleosts, either in addition to or instead of the effects from WGD.…”
Section: Discussionmentioning
confidence: 99%
“…2a) based on the traditional ichthyolith description system (Doyle and Riedel, 1979). Given that variation in tooth length can be used as an indicator of variation in the body sizes of pelagic fish (Britten and Sibert, 2020), we attempted to predict the lengths of teeth automatically, by approximating the detected contours of each tooth within a rectangle and measuring the length of the longest side (Fig. 2b).…”
Section: 3 Measurement Of Ichthyolith Lengthmentioning
confidence: 99%
“…In addition, ichthyoliths are regarded as indicators of depositional environments recently. The productivity of pelagic fish has been measured based on the accumulation rate of ichthyoliths (Sibert et al, 2014(Sibert et al, , 2016(Sibert et al, , 2020Sibert and Rubin, 2021), the evolution of pelagic ecosystems has been explored based on variations in morphotypes (Sibert et al, 2018;Sibert and Rubin, 2021), and the distribution of pelagic fish has been studied based on variation in the length of fish teeth (Britten and Sibert, 2020). Hence, establishing an effective method for ichthyolith observation will enable understanding of the records on the evolution of pelagic realms which has long been a black box in Earth science.…”
mentioning
confidence: 99%
See 1 more Smart Citation